Anopheles gambiae phagocytic hemocytes promote Plasmodium falciparum infection by regulating midgut epithelial integrity - Victor Cardoso-Jaime; George Dimopoulos (Nature Communications)
Abstract For successful transmission, the malaria parasite must traverse tissue epithelia and survive attack from the insect’s innate immune system. Hemocytes play a multitude of roles in mosquitoes, including defense against invading pathogens. Here, we show that hemocytes of the major malaria vector Anopheles gambiae promote Plasmodium falciparum infection by maintaining midgut epithelial integrity by controlling cell proliferation upon blood feeding. The mosquito’s hemocytes also control the midgut microbiota and immune gene expression. Our study unveils novel hemocyte functions that are exploited by the human malaria parasite to evade the mosquito’s immune system.